Hubungan Inisiasi Menyusui Dini (IMD) terhadap Status Gizi Bayi Dibawah Dua Tahun (BADUTA) di Puskesmas Malaka Kecamatan Lalabata Kabupaten Soppeng - Aspiati Haji Ali; Arlin Adam; Andi Alim (Puslitbang Sinergis Asa Professional, 2019)
Early Initiation Coverage (IMD) for Soppeng District based on survey data on nutritional status monitoring is still relatively low compared to the national target of 80%. So it is thought to have an impact on the prevalence of malnutrition by 22.6%, stunting 38.7%, skinny 7.7% and fat 4.5%. The purpose of this study was to look at the relationship between Early Breastfeeding Initiation and nutritional status of infants under two years at the Malaka community health centre, Lalabata District, Soppeng Regency, South Sulawesi Province. This study used a survey method with a statistical analysis approach and cross-sectional study design. The sample size in this study was 67 people which obtained through simple random sampling. This research was conducted in the working area of ​​the Malaka Health Center in Lapajung Sub-district, Lalabata District from April to June 2019. The data was processed by using the Kolmogorov-Smirnov test with a probability value of 95% in SPSS. The results of the analysis of nutritional status in infants under two years based on body weight according to the average age showed that 85.1% have good nutritional status, 10.4% less nutritional status and 4.5% over nutritional status. The nutritional status based on height according to the average age showed 65.7% had normal height, 19.4% short height and 7.5% poor height. Meanwhile, based on body weight according to a height, the result showed that 83.6% had normal weight, 11.9% under weight, and 3.0% overweight. From the results of the analysis it was found that there is no relationship between Early Breastfeeding Initiation (IMD) and the nutritional status of infants under two years in the working area of ​​the Malaka Puskesmas Lapajung Village. This happens because there are still many factors that affect nutritional status in addition to Early Breastfeeding Initiation. Therefore, it is better to conduct further research by adding research variables including sanitation and parenting.